Growth Of Single-Walled Carbon Nanotubes Through Pengethanol Colloidal Solution - Seah, Choon Ming (2011)
Since the discovery of carbon nanotubes (CNTs), powder form catalyst support becomes the dominant in this field. But powder form catalyst support possesses some shortcoming such as difficulty in catalyst size monitoring and required subsequent purification. In this study, CNTs were grown over iron nanoparticles prepared by spin coated iron nitrate that diluted in colloidal solution of absolute ethanol and polyethylene glycol (PEG). The colloidal solution was later spin coated on silicon wafer and through catalytic chemical vapor deposition (CCVD) to grow CNTs. This approach competently overcomes the shortcomings aforementioned. In order to understand the effects of various process parameters on the topography of iron nanoparticles obtained and morphology of the as-grown CNTs, all the process parameters were studied separately. The parametric study was done in three stages, representing colloidal solution (composition of colloidal solution and concentration of iron nitrate), spin coating (spin speed, angular acceleration and spin period) and CCVD (reaction temperature, methane partial pressure and reaction period) study. Iron nitrate with concentration of 40mmol/L diluted in colloidal solution at a ratio 1:1 (v/v) of absolute ethanol to PEG-400, spin coated on silicon wafer at 8000 rpm for 30 seconds and under angular acceleration of 300rpm/sec was the best parameter to distribute iron nanoparticles evenly and in small size. This catalyst sample could grow single-walled CNTs (SWCNTs) with the highest selectivity and uniformity in diameter. Piranha solution was found useful to render the hyrophobicity of silicon oxide by introducing –OH group on the wafer.